Role of Chitosan on Some Physical Properties and the Urea Controlled Release of the Silk Fibroin/Gelatin Hydrogel - Rattanamanee A. (Springer New York LLC, 2014)
Natural polymers are widely used as biodegradable matrices for the controlled release technology because they can improve the performance of the materials and make them environmentally friendly. In this work, the silk fibroin (SF)/gelatin hydrogel with chitosan (CS) was prepared by solvent casting aiming to reduce the rate of urea release from the hydrogels. Results from the Fourier transform infrared confirmed that no intermolecular interactions had taken place after the addition of CS into the SF/gelatin. Furthermore, the increase of CS content in the SF/gelatin blended hydrogels caused the decrease in their porosity that affected the increase in their crystallinity, degree of swelling, water solubility, and surface hydrophobicity. The rate of urea release from the hydrogels also depended on the content of CS of which its value of diffusion exponent characteristics (n) determined from the Korsmeyer-Peppas model for SF/gelatin/CS hydrogels were greater than 1.0. This indicated that the urea release from the SF/gelatin hydrogels with CS was a super case II transport type. Moreover, the urea release rate (k) of the SF/gelatin/CS hydrogels was lower than that of the SF/gelatin hydrogel itself indicating an extension of the urea release from the SF/gelatin hydrogels by CS which could be utilized for controlled release applications.